2022
DOI: 10.1186/s40478-022-01322-x
|View full text |Cite
|
Sign up to set email alerts
|

Proximity proteomics of C9orf72 dipeptide repeat proteins identifies molecular chaperones as modifiers of poly-GA aggregation

Abstract: The most common inherited cause of two genetically and clinico-pathologically overlapping neurodegenerative diseases, amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), is the presence of expanded GGGGCC intronic hexanucleotide repeats in the C9orf72 gene. Aside from haploinsufficiency and toxic RNA foci, another non-exclusive disease mechanism is the non-canonical translation of the repeat RNA into five different dipeptide repeat proteins (DPRs), which form neuronal inclusions in affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 112 publications
(155 reference statements)
0
25
0
Order By: Relevance
“…Three neurodegenerative mechanisms are implicated in C9ORF72 -ALS/FTD pathology: loss of function due to reduced C9ORF72 transcript and proteins levels [ 2 ], a gain of function due to the formation of RNA foci [ 46 ], and a gain of toxic function, due to the generation and accumulation of five different dipeptide repeat proteins (DPRs), via repeat-associated non-AUG (RAN) translation of hexanucleotide repeat sequences from both sense and antisense strands [ 20 ]. Of the five DPR species, there is evidence for a toxic gain-of-function role for PolyGA, PolyGR, and PolyPR aggregates in promoting neurodegeneration in affected brain areas [ 30 , 36 , 40 ]. Previous studies have established that the positively charged arginine-rich PolyGR and PolyPR proteins, and the highly insoluble PolyGA aggregates are extremely toxic in neurons [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three neurodegenerative mechanisms are implicated in C9ORF72 -ALS/FTD pathology: loss of function due to reduced C9ORF72 transcript and proteins levels [ 2 ], a gain of function due to the formation of RNA foci [ 46 ], and a gain of toxic function, due to the generation and accumulation of five different dipeptide repeat proteins (DPRs), via repeat-associated non-AUG (RAN) translation of hexanucleotide repeat sequences from both sense and antisense strands [ 20 ]. Of the five DPR species, there is evidence for a toxic gain-of-function role for PolyGA, PolyGR, and PolyPR aggregates in promoting neurodegeneration in affected brain areas [ 30 , 36 , 40 ]. Previous studies have established that the positively charged arginine-rich PolyGR and PolyPR proteins, and the highly insoluble PolyGA aggregates are extremely toxic in neurons [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another approach would be to reduce DPRs burden within motor neurons. One method involves the overexpression of heat shock protein B8 (HSPB8), which led to the increase in the autophagy-mediated degradation of DPRs, and enabled the clearance of aggregation prone proteins before they could convert into inclusions ( Liu et al, 2022 ). Furthermore, an interesting natural compound called berberine has been shown to influence TDP-43 protein aggregations boosting its degradation via autophagy ( Chang et al, 2016 ).…”
Section: Therapeutic Strategies For Targeting Alp In C9orf7...mentioning
confidence: 99%
“…Since R and D are highly charged residues, conventional immunoprecipitation/proteomics analysis, which requires cell lysis, may lead to artificial interactions during the lysis/immunoprecipitation process. To investigate the protein–protein interactions while maintaining spatial information, we performed TurboID-mediated proximity biotin labeling of the proteomes in close proximity to each R-MCD ( Figure 3 A) [ 17 , 18 ]. The visualization of biotinylated proteins using AlexaFluor488-conjugated streptavidin revealed that TurboID-(DR) 50 exclusively biotinylated proteins in nuclear speckles, and TurboID-(D 16 R 16 ) 3 biotinylated the proteins in the nucleolus, as expected ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%